Impact of student academic support on student engagement: the mediating role of basic psychological needs and academic motivation - Wei, Mun Chin; Ahmad, Nor Aniza; Ismail, Ismi Arif; Alias, Siti Noormi (UiTM Press, 2024)
The global pandemic has further complicated the task of promoting student engagement (SE), as traditional classroom settings have been disrupted. Therefore, understanding and addressing students' challenges in physical and remote learning environments have become crucial. The study aimed to examine the relationships among proposed variables and test the serial mediating role of basic psychological needs (BPN) and academic motivation (AM) in the relationship between student academic support (AS) and SE. This study utilized Structural Equation Modeling to test the proposed relationships and assess the mediating role of BPN and AM of 461 respondents in a Malaysian public research university. The structural model analysis revealed that BPN and AM significantly and positively predicted student engagement. Student AS was also found to be a positive and significant predictor of BPN, but a negative and significant predictor of academic motivation. Additionally, BPN significantly and positively predicts academic motivation. Testing the serial mediating effect demonstrated that BPN and AM mediate the relationship between student AS and engagement. This study suggests that undergraduate students in a Malaysian public university require peer and other forms of AS to enhance their learning engagement. Peer AS can positively or negatively impact academic motivation.